The Development of the Role Playing-Make a Match Model to Improve Collaboration Skills of 1st Grade Students with Syllable Material at SDN Tamansari II - Diana, Dewi Rafika Nur Diana; Ludfi Arya Wardana; Shofia Hattarina; Sriwijayanti, Ribut Prastiwi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research conducted in grade 1 of SDN Tamansari II, can be analyzed from the teaching and learning activities carried out, namely, lack of collaboration skills, many students tend to divert their gaze or have a low level of focus on the topic being explained, lack of understanding of syllable formation and have not applied the role playing learning model to students. Based on the background that has been explained, the purpose of this study is to develop the Role Playing-Make a Match model to improve the Collaboration Skills of grade 1 students with syllable material at SDN Tamansari II. The use of the role playing-make a match model in the learning process has proven its ability to improve collaboration skills according to its indicators, namely, actively contributing, actively in learning, productive, flexible, responsible, respecting each other. The purpose of this development is to produce a product in the form of a role playing-make a match model guidebook to improve collaboration skills that have been tested for feasibility, practicality, effectiveness based on assessments from material/content experts, learning models, practicality of learning, non-tests of students on indicators of collaboration skills. This study uses a development model using the steps of Borg and Gall with modifications, including: 1) Information collection, 2) Planning, 3) Product development, 4) Expert validation, 5) Field trials, 6) Final product. The instruments used include: validation sheets of material/content experts, learning models, practicality of learning, non-tests of students on indicators of collaboration skills. The results of the validation of material/content experts are ≥ 9. Learning model experts are ≥ 9.7, practicality of learning is 96%, the results of the non-test on the indicators of student collaboration skills are, 8 students often appear on the indicator points and 13 students appear quite often on the indicator points of collaboration skills. Showing that the role playing-make a match model developed is valid and feasible with revision. Based on the results of the study, the development of the role playing-make a match model to improve the collaboration skills of grade 1 students with syllable material has been valid because the percentage exceeds 81% practicality, effectiveness in improving indicators of collaboration skills. Therefore, the learning model is feasible and can be used in the teaching and learning process.